Measurement of genetically modified (GM) genes in different corn products - Asicioglu, Meltem; Yalcinkaya, Burhanettin; Akgoz, Muslum (Acg Publications, 2017)
Nowadays, genetically modified (GM) plants are widely used in several commercial products. Corn, cotton, soybean and canola are the most widely consumed foods globally and their derived products have reached the global markets. Specifically, corn has the greatest diversity of approved GM events globally (a total of 130 varieties approved in one or more countries). It is one of the most widely used food and feed ingredient, highly integrated into food and feed supply chains Since GMOs carry environmental risks and human health related risks, it is required that the food and their ingredients that either contain GMOs or derived from GMOs should be labelled. In this study, we investigated the taxon-specific cauliflower mosaic virus 35S promoter region (CaMV) and Agrobacterium tumefaciens nonpalin synthase terminator (tNOS) gene in addition to the control gene of High Mobility Group (HMG). Corn-containing foods were obtained from grocery stores in Turkey. DNA extraction was performed by modified CTAB DNA extraction method for all samples and genomic DNA were extracted. The DNA extracts were screened by qPCR and it was shown that genetically modified DNA sequences of tNOS and CaMV were not present in the samples investigated. For the security of society, randomized screens should be carried out by scientist in random bases.
Keywords: Biometrology; food safety; GMO quantification; GMO screening; corn